2023
DOI: 10.1038/s43247-023-00701-z
|View full text |Cite
|
Sign up to set email alerts
|

Substantial burial of terrestrial microplastics in the Three Gorges Reservoir, China

Abstract: Hydropower dams impact the transport of microplastics from rivers to the ocean. The Yangtze River is a large source of plastics to the ocean. Here, we report microplastic concentrations and compositions across a range of size fractions for sediment samples collected in the upper and lower reaches of the Three Gorges Dam in 2008, 2015, 2019 and 2020. We find a gradual increase in microplastic abundance over time, with preferential retention of small-sized (<300 μm) microplastics in the dam reservoir sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The four polymers that were mainly detected were PE (45.81%), PP (11.79%), polyethylene terephthalate (PET; 21.54%), and polyvinyl chloride (PVC; 14.53%) (Figure 3, Table S4). According to the theoretical density of the main detected polymers, compared with the water density, they are divided into low-density (LD; <1.0 g/cm 3 ), including PE and PP, and HD (>1.0 g/cm 3 ) polymers, including PET and PVC. Most types of polymers were detected in the water samples of the hypolimnion and the least in the ETI water samples (Table S4).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four polymers that were mainly detected were PE (45.81%), PP (11.79%), polyethylene terephthalate (PET; 21.54%), and polyvinyl chloride (PVC; 14.53%) (Figure 3, Table S4). According to the theoretical density of the main detected polymers, compared with the water density, they are divided into low-density (LD; <1.0 g/cm 3 ), including PE and PP, and HD (>1.0 g/cm 3 ) polymers, including PET and PVC. Most types of polymers were detected in the water samples of the hypolimnion and the least in the ETI water samples (Table S4).…”
Section: ■ Resultsmentioning
confidence: 99%
“…As an important unit of freshwater systems, artificial barriers intercept 65% of plastic waste before it reaches the oceans and serve as key vectors for MP transport or long-term sinks for MPs. , It has been found that lakes and reservoirs are potential long-term MP accumulators, which poses a serious challenge to the water quality and safety of reservoir ecosystems. , Most studies focused on the plastic pollution have been confined to the surface water or sediments of reservoirs. A previous study shows that a large amount of plastic debris was hidden inside the ocean; however, the behavior of plastic debris hidden inside reservoirs is largely unknown. Moreover, thermal stratification (TS) is an important hydrological process in deep reservoirs that can affect the transport of matter and energy in the water column .…”
Section: Introductionmentioning
confidence: 99%
“…MNPs are supplied from various sources, including environmental processes (physical abrasion and bio/chemical degradation) and human activities (manufacturing and using polymer-based items) . MNPs with a wide range of sizes, various components, and diverse forms are widely distributed in rivers, oceans, continents, and the atmosphere. ,, Environmental MNPs are potentially concentrated in marine environments, landfills, and artificial reservoirs , due to precipitation by the adsorption of (in)­organic molecules and biomolecules on their surfaces. , Numerous researchers have collected samples from various locations and measured their composition, size, and concentration. For instance, Weiss et al estimated the mass concentration of global MP waste smaller than 5 mm on river surface water in the range of 100–1000 ng/L using the examined data from 89 rivers.…”
Section: Current Status Of Mnp Contaminationmentioning
confidence: 99%
“…It is an undisputed fact that microplastics (MPs) possess regional and even global transportable features, as evidenced by their extensive accumulation in the isolated and sparsely inhabited areas. Of particular concern are MPs within the size range for long-distance and even global transport of dust (<25 μm). ,, Since MPs are of a lower density (0.8–1.4 g cm –3 ) than dust (2.6–2.7 cm –3 ), smaller MPs (defined in this study as those within the size range of 1–25 μm) may exhibit greater mobility during atmospheric propagation and extensively participate in global transport. , Despite this, limited information is currently available about the occurrence and fate of smaller MPs, likely due to the detection limit of current identification technology (e.g., 10 μm for μ-FTIR and 1 μm for μ-Raman). , The existing literature has reported a very high proportion of smaller MPs in the atmospheric deposition samples from protected areas in the United States (70%), deep-sea sediments in the Arctic Pole (78%), and urban fjord sediments in Norway (56.3–70.1%) . Moreover, smaller MPs have been shown to be extremely hazardous to living organisms, since they are prone to translocate to the tissues, organs, or even the bloodstream. Therefore, greater attention should be paid to the much-understudied smaller MPs given their high concentration and potential toxicity. …”
Section: Introductionmentioning
confidence: 98%